Amorphization in an Ising nanowire; unconventional effects of a uniformly applied transverse field. (4th May 2017) - Kaneyoshi, T.
ABSTRACT: The phase diagrams and magnetizations of an Ising nanowire with an amorphization are investigated by the use of the effective field theory with correlations, when a uniformly transverse field is applied perpendicularly to the main axis of the nanowire. Some characteristic behaviors have been obtained in them, such as the two types of reentrant phenomena induced by an applied transverse field.